2022
DOI: 10.1098/rsif.2021.0771
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Boolean modelling reveals the influence of energy supply on bacterial efflux pump expression

Abstract: Antimicrobial resistance (AMR) is a global health issue. One key factor contributing to AMR is the ability of bacteria to export drugs through efflux pumps, which relies on the ATP-dependent expression and interaction of several controlling genes. Recent studies have shown that significant cell-to-cell ATP variability exists within clonal bacterial populations, but the contribution of intrinsic cell-to-cell ATP heterogeneity is generally overlooked in understanding efflux pumps. Here, we consider how ATP varia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 96 publications
2
11
0
Order By: Relevance
“…Small proteins governing the expression of membrane channels (including components of efflux pumps) are also key here. More recently, a study using dynamic Boolean modeling has suggested that ATP variability and energy supply may control efflux pumps, with model bacteria developing heterogeneous pulses of efflux pump gene expression, which contribute to a sustained sub-population with increased efflux expression activity [ 71 ]. The regulation of these systems and their components is discussed in greater detail below and summarized Table 1 .…”
Section: Efflux Pump Regulationmentioning
confidence: 99%
“…Small proteins governing the expression of membrane channels (including components of efflux pumps) are also key here. More recently, a study using dynamic Boolean modeling has suggested that ATP variability and energy supply may control efflux pumps, with model bacteria developing heterogeneous pulses of efflux pump gene expression, which contribute to a sustained sub-population with increased efflux expression activity [ 71 ]. The regulation of these systems and their components is discussed in greater detail below and summarized Table 1 .…”
Section: Efflux Pump Regulationmentioning
confidence: 99%
“…The previously mentioned Boolean model in [22] takes a gene regulation network and converts it into a mathematical network (sometimes referred to as a graph) where each node represents a regulator or a downstream target and is either 'on' or 'off ' . If an activator is on then it switches a downstream target on with an assigned probability.…”
Section: Single-cell Versus Population Behaviourmentioning
confidence: 99%
“…It is frequently when models and data disagree that we learn the most. These pulses are also uncovered theoretically in [22] using a subtly different mathematical approach (Boolean modelling) where probabilities are assigned to the regulatory interactions of the gene regulation network. This approach and the transcriptional pulses are discussed further in the next section.…”
Section: Gene Regulation Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…This mirrors the ATP dependence of other biomolecular pathways (Gawthrop and Crampin 2017; 2014; Qian and Beard 2006) – for example, the detailed role of ATP in shaping the dynamics of signalling cascades has recently been illustrated using quantitative modelling grounded in systems biology and thermodynamics (Forrest et al 2023). In GRNs, theoretical studies have shown that simplified GRN models (Karlebach and Shamir 2008), using coarse-grained descriptions of genes and gene expression processes, exhibit strong energy-dependent diversity in decision-making capacity (Johnston et al 2012; Kerr, Jabbari, and Johnston 2019; Kerr et al 2022). In such models of simple mutually repressing GRN motifs, increased ATP concentrations led to more attractor states (that is, distinct stable states of gene expression to which other states evolve over time), and hence to more decision-making capacity in cells.…”
Section: Introductionmentioning
confidence: 99%